Pengaruh Variasi Suhu Aktivasi Pada Proses Steam Activation Pembuatan Karbon Aktif Terhadap Massa Penyimpanan Biogas - Suriantara, I Kadek Sepi; Wijaksana, Hendra; Sucipta, Made (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstract The Integrated Agricultural System or better known as Simantri is an agricultural system that produces biogas and so farit has only been used at the digester location or the production site itself because the simantri are far from the community. Biogas can be used by residents for cooking, but with the storage of plastic bags with only a small capacity and limited capacity, there is ANG (Adsorbed Natural Gas) technology that can store more biogas capacity. The method used is the adsorption of biogas at a storage pressure of 100 psi with 70 grams of bamboo petung activated carbon as the adsorbent, which is carbonization at a temperature of , and the activated carbon was varied with the activation at , and using steam activation and using a mass flow rate of 0.050 kg?(s) of water and using a mesh size of 34-45. The results of the research in biogas storage showed that the highest mass absorption occurred at the activation temperature variation of which was able to store 35.9grams of biogas. Then for testing biogas levels, the highest levels of methane and the lowest carbon dioxide occurred at a temperature variation of 525 with a weight capable of storing 28.9 grams. Keywords: petung bamboo, biogas, ANG, activated carbon, activation temperature